Seguimiento del desarrollo de lesiones por degeneración en pollos de engorde - Almeida Paz, I. C.L. [UNESP]; Mendes, A. A. [UNESP]; Martins, M. R.F.B. [UNESP]; Fernandes, B. C.S. [UNESP]; Almeida, I. C.L. [UNESP]; Milbradt, E. L. [UNESP]; Balog, A. [UNESP]; Komiyama, C. M. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2009)
A study was carried out in the experimental facilities of FMVZ/UNESP-Botucatu, with the aim of following-up the development and the incidence of femoral degeneration (FD). A total of 305 one-day-old male broilers were housed in six pens of 5m2 each. Histological analyses of femur head collected when broilers were 0, 7, 14, 21, 28, 35, and 42 days of age were carried out. At 42 days of age, 30 birds were taken to the experimental processing plant of FMVZ for leg gross examination. Ten legs per FD score where selected, and histologically analyzed to determine the most probable age at the beginning of the lesions, and to standardize femoral degeneration lesion scores. The histological results showed that cell architecture started to disorganize at 21 days of age in the resting and proliferation zones, and that angiogenesis increased, invading the joint cartilage, The gross lesion indexes due to femoral degeneration were 22.5%, 42.5%, and 65% at 28, 35, and 42 days of age, respectively.
Follow-up of the development of femoral degeneration lesions in broilers
Keywords: Broilers; Femoral degeneration; Femoral head